2022
DOI: 10.1002/adfm.202110998
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Steam‐Induced Heterostructured Air Electrode for Protonic Ceramic Electrochemical Cells

Abstract: The development of active and durable air electrodes is of great significance to the maturity of reversible protonic ceramic electrochemical cells (R‐PCECs). This article reports the recent findings in the performance enhancement of R‐PCECs using a novel heterostructured air electrode, consisting of a double perovskite PrBaCo1.6Fe0.2Nb0.2O5+δ backbone covered with in situ exsolved nanoparticles of Nb‐deficient PrBaCo1.6Fe0.2Nb0.2−xO5+δ. Such a heterostructured electrode is induced by the benign interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 70 publications
(102 reference statements)
2
55
0
Order By: Relevance
“…The O 1s core-level spectra can be deconvoluted into three overlapping bands (Fig. 2f) [4,29,30]. The peak at around 528.7 eV is assigned to the lattice oxygen (O lat ), and the peak at around 530.8 eV is corresponding to the surface adsorbed oxygen (O ads , including O 2− , O − , and OH − ), relating to the surface defect [31].…”
Section: Xps and Tg Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The O 1s core-level spectra can be deconvoluted into three overlapping bands (Fig. 2f) [4,29,30]. The peak at around 528.7 eV is assigned to the lattice oxygen (O lat ), and the peak at around 530.8 eV is corresponding to the surface adsorbed oxygen (O ads , including O 2− , O − , and OH − ), relating to the surface defect [31].…”
Section: Xps and Tg Analysismentioning
confidence: 99%
“…Perovskite materials have received wide attention in many technologies relevant to energy storage and conversion, ranging from catalysts in solid oxide fuel cells (SOFCs) to lightabsorbing layers in solar photovoltaics [1,2]. Rational optimization strategies (such as element doping, introducing defects, and surface modification) of the A-site cation in perovskite oxides are of great significance to enhance the performance and durability [3][4][5][6][7]. Perovskite-based materials have been intensively applied as cathode materials for SOFCs, one of the most promising energy storage and conversion devices because of their high efficiency and environmental friendliness [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have been devoted to developing high-performance air electrodes for PCECs. Some double-perovskite oxides exhibit outstanding performance as air electrodes for protonic ceramic electrochemical cells due to their ability to conduct electrons, oxygen ions, and protons. Representative material systems include PrBaCo 1.6 Fe 0.2 Nb 0.2 O 5+δ (PBCFN), Ba 1– x Gd 0.8 La 0.2+ x Co 2 O 6−δ (BGLC), and PrBa 0.8 Ca 0.2 Co 2 O 5+δ (PBCC) . For instance, Xu et al reported that the PBCFN air electrode achieved 2148 mA cm –2 at a voltage of 1.3 V and 650 °C with 3% H 2 O–air and demonstrated durability for 200 h. Zhou et al fabricated PBCC air electrode and achieved a current density of 1510 mA cm –2 at 1.3 V and 600 °C with 3% H 2 O–air.…”
Section: Introductionmentioning
confidence: 99%
“…Protonic ceramic electrochemical cells (PCECs) that can fluently switch their operation modes between power-generating fuel cell (FC) and fuel-producing electrolysis cell (EC) are deemed as one of the most promising technologies for long-term and large-scale energy conversion and storage. Unfortunately, the practical application of PCECs has been largely hindered by the sluggish kinetics of proton involved oxygen reduction reaction (P-ORR) and proton involved oxygen evolution reaction (P-OER) at the air electrodes, as described in eqs and in Kröger-Vink notation.…”
Section: Introductionmentioning
confidence: 99%